Constructing Political Image in a Mediatized Local Election: Symbolic Strategies of the Prosperous Justice Party (PKS) in West Java’s 2018 Gubernatorial Campaign - Muchtar, Khoiruddin; Turmudi, Hamzah; Dwiwarman, Denny Aditya; Zakiah, Kiki (Journal of Cultural Analysis and Social Change, 2025)
The construction of political image by the Prosperous Justice Party (PKS) during the 2018 Gubernatorial Election in West Java, Indonesia, is explored in this work, using a case study method. Regarding social construction theory by Berger and Luckmann and mediatized politics, the present research projects how PKS employed symbolic, narrative, and visual strategies to attract and shape the public's discourse and electoral appeal. Based on the data available across materials used in campaigns, media content, in-depth interviews, and field observations, the study differentiates three layers of image construction: a symbolic expression of religious and cultural affiliation, a narrative arrangement of morality and public office, and a tactical visual portrayal of digital and face-to-face campaigns. The analysis shows how PKS created a double image of religiosity and nationalism by combining a military person with an Islamic cleric while imposing local Sundanese symbols. Although the campaign connected well with those from the religious and conservative persuasion, it had problems reaching out to urban and non-ideology-oriented voters. The results show that political image construction is not just a tactical concern, but is socially constructed within local cultural values and mediated communication. This research participates in a larger debate about Islamic political branding, localized electoral strategy, and the mechanisms of identity representation in modern Indonesian democracy.